A novel iron-mediated nitrogen removal technology of ammonium oxidation coupled to nitrate/nitrite reduction: Recent advances. (1st October 2022) - Zhang, Lihong; Li, Wenxuan; Li, Jie; Wang, Ya'e; Xie, Huina; Zhao, Wei
Graphical abstract: Image 1 Highlights: The coupling of Feammox and NDFO is novel and cost-effective. The comparison between this process and other denitrification technologies is summarized. The main factors affecting the coupling process and the research of the process are analyzed. The transformation forms of iron and nitrogen are two key issues in the coupling process.